Practices, values and attitudes of young people: a case study based on students of the University of Minho - Madureira, Sara (2022)
Analyzing the behaviors, values and attitudes of youth allows us to make a merciless examination of our time, helping to understand the tangled roots of our collective experience, so that, when analyzing their options, we are not only studying the present time, but also to envision the future of our society. Having said that, the present study aims to analyze the practices, values and attitudes of young people in order to better understand their current evaluative and religious tendencies. Through a quantitative methodology, students at the University of Minho were surveyed, aged between 18 and 35 years. From the conclusions it appears that young people look for more individualistic and less social occupations, allowing them moments of personal satisfaction. Regarding their religious and evaluative dimension, it was found that little or no participation in religious services and that they show high levels of justification for certain behaviors, appearing to react openly to practices that are normally disapproved of by society. Environmental Protection, Racism and Xenophobia and Gender Violence are the current topics that deserve greater concern on the part of young university students.